Regional disparities in Greece: The performance of Crete, Peloponnese and Thessaly - Yannis M. Ioannides; George Petrakos (EIB Papers, 2000)
Unequal spatial distribution of economic activity within countries continues to be important despite the significant progress of the world economy during the second half of this century. Interest in spatial processes and inequalities has recently been revived by the influential work of Barro and Sala-i-Martin (1991, 1992, 1995) and others on the trends of convergence or divergence across countries or regions, by the theoretical work of Krugman (1991) on geography and increasing returns, and by the work of Matsuyama (1995a,b) on cumulative processes in models of monopolistic competition. The recent literature is concerned with balanced development and has important implications for regional or development policies. Noteworthy in this context is the argument advanced by Kaldor (1970), namely that unequal regional development within a given country poses more serious intellectual challenges for policy than unequal development internationally. Several studies suggest that the existence of selective tendencies, convergence clubs as in Quah (1996), and asymmetric shocks in various economies have led to the persistence and exacerbation of spatial inequalities within the European Union.
Keywords: 330; Regionales Wachstum; Regionale Disparität; Griechenland